A Right to Adequate Shelter for Asylum Seekers in the European Union. Issue 2 (3rd April 2022) - Westendorp, Ingrid
ABSTRACT: Asylum seekers who enter the European Union (EU) need temporary housing while awaiting the outcome of their asylum application procedures. It is unclear, however, which conditions must be fulfilled to achieve the goal defined by the EU that asylum seekers enjoy an 'adequate standard of living', including housing. Because this goal is only described in general terms, there are large differences in asylum seekers' accommodation in and among EU member states. This article argues that multiple purposes would be served if the EU would adopt a right to adequate shelter for asylum seekers as a common accommodation standard with well described material conditions. In order to determine whether there would be a legal basis for a right to adequate shelter, and which conditions should be met, the article presents relevant sources of human right law and EU law. It also consults scholarly articles, NGO reports, blogs, and newspapers. An examination of the actual reception circumstances shows that several problems need to be addressed. Based on this analysis, I argue that the conditions for adequate shelter encompass safety, dignity, adequate structure, appropriate space and facilities, and temporariness.